2002
DOI: 10.1038/sj.eye.6700136
|View full text |Cite
|
Sign up to set email alerts
|

The assessment and management of strabismus and amblyopia: a national audit

Abstract: Aims To determine what systems are in place within ophthalmic services for the assessment and management of children suspected of having amblyopia and strabismus. To find out what methods are used for the assessment of these children. Methods A questionnaire-based study auditing 288 orthoptic departments in the UK. Results Responses were received from 75% orthoptic departments. Most hospitals employ more than one system for the assessment of strabismus and amblyopia, which is generally dependent on route of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Masked surveys posted by mail to study ophthalmic issues have had response rates of 50 to 90%. [11][12][13][14] Our lower (20%) response may be due in part to the fact that no reminder was sent. It is also possible that respondents were those with stronger opinions, which may have skewed the results, although we cannot assess whether the skew might be in favor of those who patch more or less.…”
Section: Discussionmentioning
confidence: 58%
“…Masked surveys posted by mail to study ophthalmic issues have had response rates of 50 to 90%. [11][12][13][14] Our lower (20%) response may be due in part to the fact that no reminder was sent. It is also possible that respondents were those with stronger opinions, which may have skewed the results, although we cannot assess whether the skew might be in favor of those who patch more or less.…”
Section: Discussionmentioning
confidence: 58%
“…By 1988, 99% of national health authorities had a screening programme in place. 13 14 Ferguson et al 15 and Carney et al 1 suggested the decline in strabismus surgery was a result of improved health and preschool screening. MacEwan and Chakrabarti 2 disagreed by arguing that if screening had contributed to this decrease its effect would have been noted earlier as preschool screening was established a decade before the noted decrease in the number of surgical episodes.…”
Section: Discussionmentioning
confidence: 99%
“…The New Zealand Vision Hearing Screening program, which has existed for over 40 years, attempts to screen all children at ages four to five and 11 years for vision and hearing problems; however, there is a lack of consistent evidence on the robustness of vision screening programs, 1 the best screening tests to use, the most appropriate referral criteria and which screening personnel to utilise 1,2 . Much of the current research on children's vision screening programs focuses on the efficacy of various screening tools for identifying preschool children with amblyopia, 3,4 strabismus 5 and significant refractive errors 6 . Large population‐based studies of refractive error and visual development from countries such as China, 7 Singapore, 8,9 Australia 10 and the United States 1 have been reported; however, little is known about the prevalence of visual impairment, refractive error, strabismus and amblyopia in the New Zealand population, which includes a significant proportion of Māori and Pacifica populations not sampled elsewhere, 11,12 or the efficacy of the screening methods used in this country 13 …”
mentioning
confidence: 99%